Konsep pengembangan wisata garam Madura dengan analisis SWOT - Aprilina Susandini; Darul Islam (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
This study aimed to determine the impact of salt tourism on salt farmers and the surrounding community and to find out the problems faced by salt tourism managers in Bunder Village, Pamekasan Regency. In addition, this study aims to examine and analyze the development of salt tourism in Madura. This study uses a quantitative approach. Sampling was done using the snowball sampling technique. The respondents of this study were salt farmers, village officials, tourism managers, village communities, and tourist visitors. Data collection techniques with interviews, field observations, and documentation. The analysis technique uses SWOT analysis. Based on the research results, it is known that the potential of salt land in four districts in Madura can be used as an opportunity to develop attractive salt tourism through the concept of salt tourism education (edutourism) and packaged with cultural and historical tourism. The salt tourism offered is unique, which gives visitors a different experience. The development of Madura salt tourism can be carried out optimally if there is a cooperation between academics, government, entrepreneurs, and the community